2014
DOI: 10.1007/s11869-014-0300-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated stacks’ pollutants’ dispersion and its contributions to photochemical smog formation in a heavily industrialized area

Abstract: In this study, the photochemical smog formation over a heavily industrialized area with complex terrain was investigated. A mesoscale prognostic meteorological and air pollution model was used in combination with data, which were collected by in situ and remote monitoring stations. The area of interest is a mountainous basin in north-western Greece. The intensive industrial activity in this area has resulted in effects on the air quality of the area, mainly caused by the lignite-fired power stations and the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…There was a positive correlation between the concentration of SO 2 and NO 2 and the daily duration of sunshine. Many studies also suggest that increased air pollutant concentrations in the urban environment do not typically result from sudden increases in emission, but rather from meteorological conditions that impede dispersion in the atmosphere or result in increased pollutant generation [7,[38][39][40]. Shen and Li (2016) showed that the coefficients between API and an atmospheric pressure anomaly, and precipitation and wind speed, are always negative at the studied time scales [10].…”
Section: Meteorological Conditions At the Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…There was a positive correlation between the concentration of SO 2 and NO 2 and the daily duration of sunshine. Many studies also suggest that increased air pollutant concentrations in the urban environment do not typically result from sudden increases in emission, but rather from meteorological conditions that impede dispersion in the atmosphere or result in increased pollutant generation [7,[38][39][40]. Shen and Li (2016) showed that the coefficients between API and an atmospheric pressure anomaly, and precipitation and wind speed, are always negative at the studied time scales [10].…”
Section: Meteorological Conditions At the Surfacementioning
confidence: 99%
“…In particular, meteorological conditions control the occurrence of haze pollution [3,[7][8][9][10][11][12][13][14][15][16][17][18][19]. In China, most studies are focused on the Jingjinji area (Beijing), the Yangtza river delta (Shanghai), and the Pearl River delta (Guangzhou, Zhujiang).…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on the evaluation of the performance of the air pollution model (TAPM) in the region of Western Macedonia, Greece. Despite some attempts to evaluate TAPM in a mountainous terrain (Triantafyllou et al 2011;Aidaoui et al 2014;Matthaios et al 2016), from the current bibliography and as far as the authors are aware, this is the first detailed and long-term attempt to evaluate TAPM in a mountainous complex terrain area. However, there have been several studies concerning the model's performance in a coastal and/or flat terrain.…”
Section: Introductionmentioning
confidence: 96%
“…With the continuous consumption of oil resources and increasing environmental problems, it has become a global urgency to push the exploration of renewable energy sources such as the wind and solar energy. The key is to develop an efficient, low‐cost, and environmentally friendly energy storage device .…”
Section: Introductionmentioning
confidence: 99%